Implementasi Hukum Pidana terhadap Tindak Kekerasan di Lingkungan Pendidikan Tinggi: Analisis Sistem Peradilan Pidana atas Kasus Pembacokan Mahasiswi di Pekanbaru - Mohammad Waes Alqorni (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study is motivated by a violent incident involving the stabbing of a female student within the premises of Universitas Islam Negeri Sultan Syarif Kasim Riau, which raises concerns regarding the effectiveness of the implementation of criminal law in higher education institutions. As an academic environment, a university is expected to ensure safety and legal protection for its academic community. However, this incident reveals gaps in preventive mechanisms and in the integration of criminal case management within the campus setting. This research aims to analyze the implementation of criminal law in the case from the perspective of the criminal justice system and to assess its conformity with the principles of criminal liability and due process of law. The study employs a normative juridical method, utilizing statutory, conceptual, and case approaches, supported by document analysis and media reports. The findings indicate that the perpetrator’s conduct fulfills the elements of aggravated assault, as reflected in the presence of both actus reus and mens rea. Furthermore, the initial stages of investigation and inquiry were conducted in accordance with applicable criminal procedural law. Nevertheless, the integration between the criminal justice system and campus-based preventive policies remains suboptimal. This study recommends strengthening inter-institutional coordination and enhancing preventive measures within higher education institutions in order to establish a more comprehensive and equitable system of legal protection